Isolevuglandins Scavenger Ameliorates Myocardial Ischemic Injury by Suppressing Oxidative Stress, Apoptosis, and Inflammation - Guo, Junjie; Xu, Fengqiang; Ji, Hongwei; Jing, Yajun; Shen, Li; Weng, Xinyu; Hu, Longgang (Frontiers in Cell and Developmental Biology, 2022)
Increased levels of reactive isolevuglandins (IsoLGs) are associated with cardiovascular disease. The role of IsoLGs in myocardial infarction (MI) is unknown. Here we studied the role of IsoLG scavenger 2-hydroxybenzylamine (2-HOBA) in post-Infarction cardiac repair. We observed that infarct cardiac tissue expressed a high level of IsoLG in mice. Following MI injury, 2-HOBA treated mice exhibited smaller myocardial infarction along with improved heart function compared with control littermates. Moreover, 2-HOBA effectively attenuated MI induced cardiac remodeling, oxidative stress, apoptosis, and inflammation. Whereas, 4-hydroxybenzylamine (4-HOBA), a less reactive isomer of 2-HOBA, barely antagonized the MI-induced injury. These findings suggest that methods to reduce IsoLGs may be useful for MI therapy.